Інтернаціоналізація європейського освітнього простору: етапи розвитку та пріоритетні завдання - Чернякова, Жанна (Studies in Comparative Education, 2013)
У статті проаналізовано нормативні офіційні документи, встановлено та схарактеризовано основні етапи розвитку інтернаціоналізації європейського освітнього простору: початковий, активізації співробітництва, багаторівневої координації та інтеграції. Окреслено пріоритетні завдання розвитку інтернаціоналізації європейського освітнього простору (забезпечення рівного доступу до здобуття освіти, розвиток міжнародного освітнього партнерства, формування компетентностей європейського вчителя та ключових компетентностей громадянина Європи, запровадження політики мультилінгвізму, європейських стандартів якості освіти). В статье проанализированы нормативные официальные документы, установлены и охарактеризованы основные этапы развития интернационализации европейского образовательного пространства: начальный, активизации сотрудничества, многоуровневой координации и интеграции. Определены приоритетные задачи развития интернационализации европейского образовательного пространства (обеспечение равного доступа к получению образования, развитие международного образовательного партнерства, формирование компетентностей европейского учителя и ключевых компетентностей гражданина Европы, введение политики мультилингвизма, европейских стандартов качества образования). The entry of Ukraine into the global and European educational space leads to a qualitative transformation of education in line with the international development tendencies. The internationalization of education is a priority vector of current educational policy in Europe and the world. Spreading the process of internationalization of education at all levels of educational space needs the study of the works of foreign authors who characterize the educational space from the standpoint of multidimensionality and polisubjectivity. The analysis of current strategies of internationalization which reveals essential changes, determines the means of modern educational transformations focused on the specific measures at different levels of European education, can identify the major challenges of internationalization of education. A comprehensive overview of the specific strategies of internationalization of education enables the study of the official documents, which directly covers the actual state and prospects of internationalization of education at the international, European, national, regional, institutional levels. The analysis of the official documents that set out the program of action of the internationalization of educational space, allows to identify the main stages of the internationalization of European educational space (initial, increased cooperation, multilevel of coordination and integration). The priorities of internationalization of educational space are defined: the development of cooperation between the EU countries, the spread of the progressive school practice in order to improve the basic skills of students, the formation of professional competence of graduates who meet the requirements of the modern labor market, the modernization of higher education in the context of internationalization (introduction of internationalized curriculum, academic mobility, quality assurance of internationalized education and vocational teacher training teachers), ensuring equal access to education, the use of progressive experience in international education, the implementation of educational innovations, the development of partnerships between European suppliers of educational services, research institutes and others. The author of the article outlines the priorities of internationalization of European education space: ensuring equal access to education, promoting maintaining peace and stability in the region and the world, the development of international education partnerships, formation of professional competencies of the teachers and the European key competences of the citizen of Europe, the introduction of the multilingualism policy.